Discrete H [infinity] optimization with applications in signal processing and control systems - Chui, C. K. (Springer series in information sciences, 1997)
Talks about optimization for digital signal processing and discrete-time control systems. Providing readers with sufficient background in the subject to enable them to begin research in this field, this book includes rigorous derivations of the results, many examples as well as the discussion of research problems.